Re: Prediction of microcephaly at birth using three reference ranges for fetal head circumference: can we improve prenatal diagnosis? Z. Leibovitz, E. Daniel‐Spiegel, G. Malinger, K. Haratz, M. Tamarkin, L. Gindes, L. Schreiber, L. Ben‐Sira, D. Lev, I. Shapiro, H. Bakry, B. Weizman, A. Zreik, S. Egenburg, A. Arad, R. Tepper, D. Kidron and T. Lerman‐Sagie. Ultrasound Obstet Gynecol 2016; 47: 586–592. (May 2016) - Deter, R. L.
Abstract : Linked Comment: Ultrasound Obstet Gynecol 2016; 47: 586–592